If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xsquared + x + -12 = 0 Reorder the terms: -12 + adeqrsuX + x = 0 Solving -12 + adeqrsuX + x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12' to each side of the equation. -12 + adeqrsuX + 12 + x = 0 + 12 Reorder the terms: -12 + 12 + adeqrsuX + x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + adeqrsuX + x = 0 + 12 adeqrsuX + x = 0 + 12 Combine like terms: 0 + 12 = 12 adeqrsuX + x = 12 Add '-1x' to each side of the equation. adeqrsuX + x + -1x = 12 + -1x Combine like terms: x + -1x = 0 adeqrsuX + 0 = 12 + -1x adeqrsuX = 12 + -1x Divide each side by 'deqrsuX'. a = 12d-1e-1q-1r-1s-1u-1X-1 + -1d-1e-1q-1r-1s-1u-1xX-1 Simplifying a = 12d-1e-1q-1r-1s-1u-1X-1 + -1d-1e-1q-1r-1s-1u-1xX-1
| 6x^2+12x+4=1 | | 7(2-3x)-5(6+x)+4x= | | K-11=22 | | xsquared+24x+39= | | -2(3x-1)=-4x-8 | | 14y=-23y-17-10 | | X^2+16x+64=144 | | 28x+4x-6=0 | | 2611900(15+x)= | | 30+d^2=11d | | Z+5.4=6.3 | | (x+6)-(5-2x)=0 | | .5x+1.333x=x+10 | | .13x+.5y=.25 | | 3x-18=16x+8 | | 9x+6=6x+12 | | 7x-13+4x-9+2x+2=180 | | 4a^2=12a | | -5f-14=2f | | 2(f-8)=-6 | | x*4=40 | | -8.3-4.5=1.7n-0.7n-9.9 | | 8x-(4x+16)=16 | | 36-2y=-37 | | 18-2y=-37 | | 8(3x-2)-(4x-3)=6(4-x) | | 8x(4x+4)=16 | | Y=ln(e^3x) | | (-6)-32+22= | | 16=32x | | 2w+2(w+2)=32 | | 10(s-7)=-113 |